Daily Challenges of Polish Language Teachers in Working with Students of Ukrainian Origin - Mazowiecka, Kornelia; Tatar, Wiktoria (Activation – innovation – acculturation. (Glotto)didactics and the migration crisis, 2024)
The article highlights the issues faced by teachers in primary and secondary schools who teach newly arrived students of Ukrainian origin. A survey was created to reflect on ways to improve the situation for Polish language teachers. The authors asked questions regarding the lessons conducted, such as whether the presence of non-native children and adolescents affects the quality of the classes, and, importantly, whether the teachers have educational backgrounds in glottodidactics. They also inquired about how the teachers would explain typically grammatical issues. The study reveals that Polish schools still face the same problems as they did at the beginning of the influx of foreigners into educational institutions. Based on the collected material, the conclusion emerged that the situation remains difficult for both sides – teachers and students – and requires improvement.